Thyroid nodules and cancer during pregnancy, post-partum and preconception planning: Addressing the uncertainties and challenges. Issue 4 (July 2020) - Papaleontiou, Maria; Haymart, Megan R.
Abstract : Thyroid nodules and thyroid cancer have become increasingly common worldwide. When discovered during pregnancy, they pose unique diagnostic and therapeutic challenges for both the treating physician and the patient. The benefits of treatment should be carefully weighed against risks that may adversely impact maternal and fetal health. In this review, we present current knowledge and controversies surrounding the management of thyroid nodules and thyroid cancer in pregnancy, in the post-partum period and during preconception planning.